2015
DOI: 10.1126/scitranslmed.aaa3236
|View full text |Cite
|
Sign up to set email alerts
|

Arterial microanatomy determines the success of energy-based renal denervation in controlling hypertension

Abstract: Renal Denervation (RDN) is a treatment option for patients with hypertension resistant to conventional therapy. Clinical trials have demonstrated variable benefit. To understand the determinants of successful clinical response to this treatment, we integrated porcine and computational models of intravascular radiofrequency RDN. Controlled single-electrode denervation resulted in ablation zone geometries that varied in arc, area and depth, depending on the composition of the adjacent tissue substructure. Comput… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 45 publications
(68 reference statements)
1
39
0
Order By: Relevance
“…[21][22][23] This study strongly suggests that renal sympathetic nerves attempt to regenerate but without apparent functional reconnection based on persistent NE level suppression. 14,[24][25][26] The high degree of distal nerve atrophy observed at 7 and 30 days in this study reported at chronic time points in other large animal experiments where RF ablation of renal nerves was performed. 14,20 It is necessary to further establish if the apparent morphological "recovery" of distal nerves could be responsible for the late increase in NE levels and whether this partial recovery may or may not produce a physiologic increase in blood pressure.…”
Section: Discussionsupporting
confidence: 55%
“…[21][22][23] This study strongly suggests that renal sympathetic nerves attempt to regenerate but without apparent functional reconnection based on persistent NE level suppression. 14,[24][25][26] The high degree of distal nerve atrophy observed at 7 and 30 days in this study reported at chronic time points in other large animal experiments where RF ablation of renal nerves was performed. 14,20 It is necessary to further establish if the apparent morphological "recovery" of distal nerves could be responsible for the late increase in NE levels and whether this partial recovery may or may not produce a physiologic increase in blood pressure.…”
Section: Discussionsupporting
confidence: 55%
“…35 Nerve injury and ablation also appears to be determined by tissue microanatomy at the electrode site, with power density peaking at discontinuities between fatty adventitia and water-rich tissues. 36 The duration of the BP-lowering effect has also been a matter of discussion because there are reports that point to the fact that renal fibers may regenerate and regrow into functionally active nerves. 37 However, studies with long follow-ups (up to 36 months, Table 1) show that BP remains significantly lower than baseline after RDN.…”
Section: The Sympathetic Nervous System and Renal Anatomy-a Very Closmentioning
confidence: 99%
“…30 An animal study showed that the ablation zone geometries varied in arc, area and depth, depending on the composition of the adjacent tissue substructure. 31 In addition, the delivered power density was influenced by tissue substructure and peaked at the conductivity discontinuities between soft fatty adventitia and water-rich tissues, not at the electrode-tissue interface. 31 With a greater recognition of nerve distribution, the ablation depth and location should be taken carefully into account.…”
Section: Discussionmentioning
confidence: 98%